2019
DOI: 10.1177/1724600819834235
|View full text |Cite
|
Sign up to set email alerts
|

New and old biomarkers in the differential diagnosis of lung cancer: Pro-gastrin-releasing peptide in comparison with neuron-specific enolase, carcinoembryonic antigen, and CYFRA 21-1

Abstract: Background: Testing for circulating biomarkers in lung cancer is hampered by the insufficient specificity. We aimed to assess the relative diagnostic accuracy of pro-gastrin-releasing peptide (ProGRP) for the differential diagnosis of small cell lung cancer and compare it with more conventional biomarkers. Methods: We enrolled a cohort of 390 patients with a clinical suspicion of lung cancer and for whom a histologic assessment was available. Serum or plasma samples were assessed for ProGRP, carcinoembryonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…When looking at the diagnostic performance of 6 biomarkers individually on histologic types, NSE, HE4, and ProGRP showed relative high AUC sensitivity and speci city, with ProGRP presenting the highest speci city for SCLC. These results are similar with other reports on ProGRP [26][27][28].…”
Section: Diagnostic Performance Of 6 Biomarkers On Histological Typessupporting
confidence: 93%
“…When looking at the diagnostic performance of 6 biomarkers individually on histologic types, NSE, HE4, and ProGRP showed relative high AUC sensitivity and speci city, with ProGRP presenting the highest speci city for SCLC. These results are similar with other reports on ProGRP [26][27][28].…”
Section: Diagnostic Performance Of 6 Biomarkers On Histological Typessupporting
confidence: 93%
“…However, our results with more combined TMs did not display better diagnostic efficacy, and the feasibility of this diagnostic panel required further assessment of cost-effectiveness analysis. Mauro et al 16 ran a multivariable logistic regression analysis to quantify the added value of ProGRP to other conventional markers including ProGRP, NSE, CEA, and CYFRA 21-1, but no markers improved the performance of ProGRP in the diagnosis of SCLC with respect to benign lung disease. In our study, the logistic regression predictive model including SCC, NSE, and ProGRP obtained a preferable efficacy (AUC: 0.888; 95% CI: 0.846–0.929; sensitivity: 71.3%; specificity: 95.0%).…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 The diagnostic performance of ProGRP and NSE individually seemed better than other conventional tumor markers for SCLC; however, there are still some deficiencies. 1618 Some researchers attempted to improve their diagnostic efficacy in combination with other tumor markers including CEA, TPA, TPS, SCC, CA125, CA19-9, HE4, and CYFRA 21-1, etc. 9, 1925 However, no consensus has been reached with respect to tumor markers’ combined pattern in SCLC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Serum tumor markers remain a simple and economical tool for diagnosing and predicting the prognosis of lung cancer patients. Many serum components such as CEA, CYFRA 21-1, SCC, and NSE have been investigated and considered to be markers of this malignancy (Mauro et al 2019). With respect to the relationship of serum tumor markers and BM, previous studies have demonstrated that patients with high CEA level had a higher risk of BM and poor prognosis (Lee et al 2012).…”
Section: Discussionmentioning
confidence: 99%